1985
DOI: 10.4315/0362-028x-48.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Maple Syrup Processed from Bleach-Treated Sap

Abstract: Recently an undefined off-flavor was detected in syrup produced from sap flowing from tubing systems cleaned with bleach. To identify if bleach was the source of the off-flavor, samples of maple sap, to which various concentrations of sodium hypochlorite (a common sanitizing solution) were added, were processed to syrup. Three tasters detected off-flavors in all experimental syrups, except the control, and associated them with the sodium and chloride level. An off-flavor was described as “salty” with a minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The monosaccharide levels in maple syrup are known to increase with storage time [37]. The processing method and/or microbial load may also contribute to this change [18,41].…”
Section: Carbohydrate Contentmentioning
confidence: 99%
“…The monosaccharide levels in maple syrup are known to increase with storage time [37]. The processing method and/or microbial load may also contribute to this change [18,41].…”
Section: Carbohydrate Contentmentioning
confidence: 99%
“…Moreover, it has been shown that tracing changes in the content of tree saps may be of benefit to general environmental monitoring (haJru, huldén 1990(haJru, huldén , greenough et al 2010. Furthermore, it has been observed that the mineral content of sap determines the quality of syrups produced from it (MorSelli et al 1985, MorSelli, Whalen 1987.…”
Section: Introductionmentioning
confidence: 99%